LincRNA00494 Suppresses Non-small Cell Lung Cancer Cell Proliferation by Regulating SRCIN1 Expression as a ceRNA - Dong, Jingsi; Li, Bingjie; Lin, Dan; Lu, Dan; Liu, Chang; Lu, Xingbing; Tang, Xiaojun; Li, Lu; Zhu, Daxing; Liu, Jiewei; Qiu, Xiaoming; Tian, Long; et al. (Frontiers in Oncology, 2020)
Background: Lung cancer is the most common malignant tumors worldwide. Accumulating results shows that long non-coding RNAs (lncRNAs) play a key role in tumorigenesis. Patients and methods: 163 tumor tissues were collected from NSCLC patients from West China Hospital of Sichuan University. LincRNA00494 is a novel LncRNA, and its expression and biological effect in non-small cell lung cancer (NSCLC) were reported in the study. The cell lines of NSCLC were used in this study. Result: LincRNA00494 mainly distributes in cytoplasm. LincRNA00494 was down-regulated in tumor tissues compared with adjacent non-tumor tissues. The expression of LincRNA00494 was positively correlated with SRCIN1 (R = 0.57, P< 0.05). Silencing LincRNA00494 in cell lines substantially decreased SRCIN1 expression at mRNA and protein levels, whereas overexpression of LincRNA00494 improved SRCIN1 levels. MiR-150-3p significantly decreased the luciferase signals of LincRNA00494 and SRCIN1 reporters. After transfecting with miR-150-3p mimics and miR-150-3p inhibitor, overexpression of LincRNA00494 decreased cell proliferation of the H358 (36%) and H1299 (29%) cell lines compared with controlled by CCK-8 assay; whereas, silencing LincRNA00494 promoted the proliferation in the H358 (47%) and H1299 (35%) cells. Tumor growth from overexpressed LincRNA00494 xenograft was significantly decreased, additionally, LincRNA00494 silence observably increased tumor growth compared with the control cells. Conclusions: Functional experiments revealed that LincRNA00494 inhibited NSCLC cell proliferation, which might be related to its suppressive effect on SRCIN1, a tumor suppressor gene, acting as a decoy for miR-150-3p at the molecular level. Study data showed that LincRNA00494 might possess anti-neoplastic properties during NSCLC tumor-genesis in a ceRNA manner.